PENGARUH PENGGANTIAN DEDAK HALUS DENGAN KULIT KOPI TERHADAP PERSENTASE KARKAS DAN LEMAK ABDOMEN BROILER - Tatilu, Febriana F.; Sompie, F. N.; Imbar, Meity; Kowel, Y. H.S. (Universitas Sam Ratulangi, 2015)
THE EFFECTS OF SUBSTITUTION OF RICE BRAIN WITH COFFEE PULP ON BROILER’S CARCASS AND ABDOMINAL LIPID PERCENTAGES. A research evaluating the effects of substitution of rice brain with coffee pulp on broiler’s carcass and abdominal lipid percentage has been conducted at Faculty of Animal Science. Sixty unsexed broiler’s strain Hubbard were used in this experiment. The chicks were allocated into 20 units of cages. A Completely Randomized Design (CRD) was used with 4 treatments and 5 replications. The treatments were R0 (0% coffee pulp), R1 (7% coffee pulp), R2 (14% coffee pulp) and R3 (21% coffee pulp). Variable measure were : carcass percentage and abdominal lipid percentage. Anova showed that there were higly significant effects of treatment on carcass and abdominal lipid percentages. Honestly Significant Difference (HSD) test showed that there were no significant difference on carcass percentage among R0 (72.77%), R1 (71.96%), and R2 (71.45%), however percentage carcass of R3 (67.41%) significantly lower compared to R0, R1, and R2. There were no significant difference abdominal lipid percentage of R0 (1.78%) and R1 (1.70%). R0 and R1 were significantly higher compared to R2 (1.15%) and R3 (0.88%), however R2 was significantly higher compared to R3. It is concluded that the substitution of rice brain with 14% coffee pulp was the best effects on carcass and abdominal lipids of broiler. Keyword : coffee pulp, broiler, carcass percentages, abdominal lipid.